Trade Integration in Sub-Saharan Africa: Lessons for Malawian Trade Policy - Douillet, Mathilde; Pauw, Karl (International Food Policy Research Institute, 2012)
Trade integration is a potentially powerful driver of economic growth in developing countries, particularly if it creates export opportunities and promotes value addition in manufacturing sectors. Given the prominence of agriculture in Sub-Saharan African countries—both as a source of employment and as an earner of foreign exchange—increased market access for agricultural exports is a common interest in these countries’ trade negotiations. Trade negotiations, however, typically involve a complex set of interactions, bilaterally, regionally, or multilaterally. Therefore, countries need to understand how they might be affected by these agreements, and also how different agreements might interact with one another. This brief provides some insight on the matter for Sub-Saharan Africa in general, and Malawi in particular, based on simulations of actual, proposed, or hypothetical trade integration scenarios.